Expert insights on Hodgkin’s lymphoma development in an activated PI3K delta syndrome patient undergoing leniolisib treatment - Conti, Francesca; Moratti, Mattia; Sabattini, Elena; Zinzani, Pier Luigi (Frontiers in Immunology, 2025)
Activated PI3K delta syndrome (APDS) is a primary immunodeficiency that is caused by mutations in the PI3K signalling pathway resulting in either gain-of-function or loss-of-function phenotypes of APDS 1 and 2. Malignancy is one of the most serious complications associated with APDS patients, with the most commonly occurring of these being lymphoma, and is the most common cause of death in APDS patients. Management of APDS is complex and variable due to the heterogeneous nature of the disease and ranges from antimicrobial and immunosuppressant agents to haematopoetic stem cell transplantation. More recently, an increasing level of interest has been shown in the use of more targeted agents such as PI3Kδ-specific inhibitors. Here, we provide expert perspective on the suspected causality of a case of lymphoma observed in a 20-year-old female patient who was included in a clinical trial of leniolisib, a PI3K inhibitor.